New concept: "TARN friendly trauma reporting" (what radiologists say really does matter). Issue 8 (August 2021) - Jenkins, P.; Coates, P.; Fong, J.; Eccles, A.; Drake, L.; Hudson, T.
Abstract : AIM: To establish if detailed review of trauma reports with reference to coding manual improved accuracy of ISS and to establish if demonstrated changes in coding affected performance and tariff payment. MATERIALS AND METHODS: A study was undertaken which gathered data from 6 months across the five trusts with information on imaging undertaken, mechanism of injury (MOI), Injury Severity Score (ISS), and injury descriptors was included. Patients with ISS near to a best practice tariff boundary of 9 and 16 (5–8 and 11–15) then had their imaging reviewed by the Radiology Department with direct reference to the ISS coding manual. Injuries were then re-coded and ISS recalculated. RESULTS: Over the 6-month period, 1, 693 patients were admitted to the database from the five hospitals. One hundred and sixty-nine (9.9%) patients met the inclusion criteria for review. Thirty-five (20.7%) had a change in abbreviated (region specific) injury code, with 30 a change in the resultant ISS. Three had a decrease in ISS and 27 increased ISS with all 27 moving across an ISS best practice tariff and three moving across two payment tariff boundaries. With re-coding, there was a potential £15, 000 of lost revenue from the major trauma centre (MTC) alone. CONCLUSION: Reporting with reference to ISS description improves the accuracy of ISS significantly. Radiologists improving the descriptions of specific injury patterns and adopting 'Trauma Audit and Research Network friendly' reporting strategies may improve data accuracy, performance, and payment of best practice tariffs to hospitals. Highlights: The style of radiologists' report affects hospital performance and income. Reporting with reference to injury score descriptors improves accuracy. Around 20% of cases changed their injury score when reviewed.